Curriculum and Pharmacy practice experience offered for Pharm-D in Pakistan: needs and possibilities - Madiha, Madiha; Yang, Chang-qing (International Current Pharmaceutical Journal, 2014)
Pharm-D program was implemented 10 years ago in Pakistan in 2004. Since then perception of pharmacist as a health care professional became somewhat clearer among public but due to less availability of resources in Pakistan, their practice is so limited. Pharmacy Council of Pakistan has revised Pharm-D curriculum in 2011. Before this up gradation some academicians have highlighted lacking in previous curriculum, but many of them are still there in new updated syllabi. In this review we have presented a sketch of current pharmacy education and practice in Pakistan especially focusing Pharm-D curriculum. In the end by considering pharmacists current role, limitations in Pharm-D course and already published interventions for advancing pharmacy education in Pakistan, we have discussed some major improvements required to be done in curriculum and pharmacy practice experiential component (clinical clerkship) offered for Pharm-D degree in Pakistan. DOI: http://dx.doi.org/10.3329/icpj.v3i8.19406 International Current Pharmaceutical Journal, July 2014, 3(8): 313-317